ANALYSIS OF INTERNAL AND EXTERNAL FACTORS AFFECTING THE LEARNING INDEPENDENCE OF STUDENTS WITH DEAF DISABILITIES IN HIGHER EDUCATION: A SYSTEMATIC REVIEW - Setia Budi; Neviyarni S; Afdal; Rara Ajeng Pratiwi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to analyze internal and external factors that influence the learning independence of deaf students in higher education through a systematic review approach. Data were obtained from 15 national and international journal articles indexed by Google Scholar, published between 2015 and 2025, which discuss the academic, socio-emotional, communication, cognitive, and learning independence aspects of deaf students. The analysis results show that learning independence is influenced by internal factors, such as motivation, self-confidence, effective learning strategies, and adaptability. External factors that play a role include family support, learning facilities, inclusive campus policies, and social support from friends and the community. Communication barriers, social stigma, and limited facilities remain significant challenges that can interfere with learning independence. This study confirms that the success of inclusive education requires an integration of personal and environmental factors. Implications: Higher education institutions need to strengthen accessibility services, families are expected to provide consistent emotional support, and further research is needed to evaluate the effectiveness of more targeted interventions.